Insights into lignocellulose degradation: comparative genomics of anaerobic and cellulolytic Ruminiclostridium-type species - You, Mengcheng; Zhao, Qiuyun; Liu, Yuansheng; Zhang, Wenhao; Shen, Zhewei; Ren, Zhenxing; Xu, Chenggang (Frontiers in Microbiology, 2023)
Mesophilic, anaerobic, and cellulolytic Ruminiclostridium type bacterial species can secrete an extracellular, multi-enzyme machinery-cellulosome, which efficiently degrades cellulose. Here, we first reported the complete genome of Ruminiclostridium papyrosolvens DSM2782, a single circular 5,027,861-bp chromosome with 37.1%G+C content and compared it with other Ruminiclostridium type species. Pan-genome analysis showed that Ruminiclostridium type species share a large number of core genes to keep conserving basic functions, although they have a high level of intraspecific genetic diversity. Especially, KEGG mapping revealed that Ruminiclostridium type species mainly take ABC transporters regulated by two-component systems (TCSs) to absorb extracellular sugars, but not phosphotransferase systems (PTSs) that employed by solventogenic clostridia, such as Clostridium acetobutylicum. Furthermore, we performed comparative analyses of the species-specific repertoire of CAZymes for each of the Ruminiclostridium type species. The high similarity of their cohesins of scaffoldins suggests a common ancestor and potential cross-species recognition. Additionally, both differences between the C-terminal cohesins and other cohesins of scaffoldins, and between the dockerins linking with cellulases and other catalytic domains indicate the preference of the location of cellulosomal catalytic subunits at scaffoldins. The information gained in this work may be utilized directly or developed further by genetically engineering and optimizing enzyme systems or cell factories for enhanced biotechnological biomass deconstruction and biofuel production.